Unequal error protection of H.264/AVC video over wireless using hierarchical QAM - Chang, Yoong Choon; Lee, Sze Wei; Komiya, Ryoichi (2007)
In this paper, unequal error protection (UEP) of H.264/AVC coded video using hierarchical quadrature amplitude modulation (HQAM), which takes into consideration the non-uniformly distributed importance of intracoded frame (I-frame) and predictive coded frame (P-frame) is proposed. In order to optimally assign the hierarchical QAM high priority (HP) and low priority (LP) bits to the H.264/AVC coded video, a low-complexity optimal allocation algorithm is also proposed. The proposed low-complexity algorithm reduces the computational complexity of the optimal allocation problem, compared with the exhaustive search process. Simulation results demonstrate that our UEP scheme outperforms the conventional UEP scheme.